n = 1 ∑ 1 0 1 ( 1 2 + 2 2 + 3 2 + ⋯ + n 2 2 n + 1 )
If the value of above expression can be written in the form B A , where A and B are positive coprime integers, find A + B .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Awawawa... I answered 708... I forgot to simplify 6 ⋅ 1 0 2 1 0 1 ...
It may be a pretty stupid question so please bare with me. In the 6th step, how and why were the summation simplified to 1 and 1/102? Thanks
Log in to reply
n = 1 ∑ 1 0 1 ( n 1 − n + 1 1 ) n = 1 ∑ 1 0 1 n 1 − n = 2 ∑ 1 0 2 n 1 1 + 2 1 + 3 1 + … + 1 0 1 1 − 2 1 − 3 1 − … − 1 0 1 1 − 1 0 2 1 1 − 1 0 2 1 = 1 0 2 1 0 1
Check out the linked wiki!
Log in to reply
Why is editing done to my solution?
Log in to reply
@Akshat Sharda – We edit some solutions to make them more presentable and easy to read.
This includes converting equations into Latex so that others can understand them at a glance, and adding explanations / justifications for steps that were taken.
Log in to reply
@Calvin Lin – Alright! If thats good for the community! :-)
Very overrated problem.
Same way buddy
Problem Loading...
Note Loading...
Set Loading...
Recall that the sum of the first n perfect squares is 1 2 + 2 2 + 3 2 + ⋯ + n 2 = 6 1 n ( n + 1 ) ( 2 n + 1 ) . (reference: sum of n, n², or n³ ).
= n = 1 ∑ 1 0 1 ⎝ ⎜ ⎜ ⎜ ⎜ ⎛ i = 1 ∑ n i 2 2 n + 1 ⎠ ⎟ ⎟ ⎟ ⎟ ⎞ = n = 1 ∑ 1 0 1 ( 6 n ( n + 1 ) ( 2 n + 1 ) 2 n + 1 ) = 6 n = 1 ∑ 1 0 1 n ( n + 1 ) 1 = 6 n = 1 ∑ 1 0 1 ( n 1 − n + 1 1 ) = 6 ( n = 1 ∑ 1 0 1 n 1 − n = 2 ∑ 1 0 2 n 1 ) = 6 ( 1 − 1 0 2 1 ) = 1 7 1 0 1 ⇒ 1 0 1 + 1 7 = 1 1 8